2000
DOI: 10.1053/euhj.1999.1945
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications and clinical outcome after coronary angioplasty with platelet IIb/IIIa receptor blockade. Comparison of transradial vs transfemoral arterial access

Abstract: Coronary angioplasty in patients treated by abciximab using the transradial approach is efficacious with fewer major access site complications than with the transfemoral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
68
1
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 23 publications
8
68
1
7
Order By: Relevance
“…A principal vantagem dessa técnica sobre a femoral já foi previamente demonstrada por estudos randomizados 28 e meta-análises 29 . Se considerarmos pacientes em uso de anticoagulantes e esquemas potentes de antiagregação plaquetária, esse benefício fica ainda mais evidente 30 . Em nosso estudo, a técnica radial foi utilizada em apenas 5,3% dos procedimentos, e esses pacientes tiveram taxas de complicações vasculares significativamente menores que aqueles tratados pela via femoral.…”
Section: Discussionunclassified
“…A principal vantagem dessa técnica sobre a femoral já foi previamente demonstrada por estudos randomizados 28 e meta-análises 29 . Se considerarmos pacientes em uso de anticoagulantes e esquemas potentes de antiagregação plaquetária, esse benefício fica ainda mais evidente 30 . Em nosso estudo, a técnica radial foi utilizada em apenas 5,3% dos procedimentos, e esses pacientes tiveram taxas de complicações vasculares significativamente menores que aqueles tratados pela via femoral.…”
Section: Discussionunclassified
“…Some authors 4,6 have reported lower complication rates with the transradial approach as compared with that with the transfemoral approach, described by Seldinger. Despite the initial favorable results, the transradial approach has a learning curve that hinders its acceptance by most interventional cardiologists.…”
mentioning
confidence: 99%
“…The transradial artery approach for coronary angiography was reported for the first time by Campeau in 1989 1 , and, since then, several groups have reported their experiences related to both the diagnosis and treatment through angioplasty using that access [2][3][4][5][6][7] . Some authors 4,6 have reported lower complication rates with the transradial approach as compared with that with the transfemoral approach, described by Seldinger.…”
mentioning
confidence: 99%
“…[5][6][7][8] Bleeding is reduced after PCI, even in patients treated with aggressive antithrombotic regimens, including abciximab. 5 Also observed with TRA are more rapid mobilization of the patient, shorter hospital stays, 6 and reduced costs. 7 Many patients appear to prefer TRA over TFA.…”
mentioning
confidence: 99%